Heirs Responsibility for a Notaries Unfinished Act Upon the Notaries Demise - Rita Bayu Astuti; Nuri Hidayati; Maruli Yanto (Universitas Islam Darul Ulum, 2025)
A Notary who dies during their tenure inevitably leaves behind unfinished work. This unfinished work specifically pertains to deeds drafted by the Notary in their capacity as the maker of an authentic instrument. Juridically, such deeds are not yet valid as authentic instruments and can be classified as unfinished Notary work at the time of death. This situation becomes the root of a legal issue because the draft deed that has not been signed is not categorized as a notary protocol. It is understood that a vacuum of norm exists in the Law on Notary concerning the responsibility for completing this unfinished work. This research aims to analyze the form of legal certainty for the completion of unfinished deed-making work when a Notary passes away. The research method used is normative-juridical, with a statutory and conceptual approach. The results show that when a Notary dies during the drafting process of a deed, where the formalization of the deed has not yet been executed, this implies that the deed remains a private agreement and does not qualify as a deed. Consequently, it is not qualified as a notary protocol. Therefore, any items entrusted by the appearers to the deceased Notary are merely limited to the rights and obligations between the parties and the Notary. This raises the question of whether the heirs are obligated to provide compensation to the appearers, especially since the heirs have limited information and knowledge about the notary office's management, which could lead to losses for them under certain conditions. The form of legal protection for the parties involves a receipt for the deposit of certificates and payment of advance fees, affixed with the notary office's stamp as a form of office management, which can facilitate the Heirs with the assistance of the office staff.